2016
DOI: 10.1016/j.scriptamat.2016.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Auger electron spectroscopy analysis of grain boundary microchemistry in an Al–Cu–Li alloy

Abstract: In situ impact fracture combined with Auger electron spectroscopy (AES) was employed to determine grain boundary (GB) microchemistry, namely lithium (Li) concentration, for an Al-Cu-Li alloy. The Li/Al ratio of GBs in the naturally aged condition was revealed to be significantly higher than in the overaged condition (or in the bulk alloy). GB fracture surfaces for the naturally aged alloy were depleted in Cu, whereas in the overaged condition the GB were depleted in Li and enriched in Cu relative to the bulk c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…These particles were Cu rich and also contained some Fe. According to the literature and the approximate composition given by the EDS analyses, the particles such as the one shown in Figure 5a, could be composed of Al 2 CuM phase ( θ’ ), or Al 2 Cu for the case of Alloy S1, where M could be one or more alloying elements, such as Li or Mg [40,41]. Others also reported the presence of Fe in the particles in the structures of similar alloys, which was attributed to the inaccuracy of the EDS measurement or the existence of iron impurities in the particle [40].…”
Section: Resultsmentioning
confidence: 99%
“…These particles were Cu rich and also contained some Fe. According to the literature and the approximate composition given by the EDS analyses, the particles such as the one shown in Figure 5a, could be composed of Al 2 CuM phase ( θ’ ), or Al 2 Cu for the case of Alloy S1, where M could be one or more alloying elements, such as Li or Mg [40,41]. Others also reported the presence of Fe in the particles in the structures of similar alloys, which was attributed to the inaccuracy of the EDS measurement or the existence of iron impurities in the particle [40].…”
Section: Resultsmentioning
confidence: 99%
“…The primary driving force for research and development on aviation aluminum alloys is to reduce the weight of aircraft [1,2,3,4]. Owing to the low density, high strength, and excellent fatigue crack resistance, Al-Cu-Li alloys have received increasing attention during the last two decades [5,6,7,8,9,10]. Being the lightest metallic element in the nature, lithium contributes to 6% increase in elastic modulus and 3% decrease in weight for aluminum alloys by adding 1 wt.% of lithium [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the amount, size, location, and chemistry of precipitated phases show significant effects on the pitting corrosion behavior of aluminum alloys [8,15,16,17,18]. Abundant studies have shown that the addition of Li can change the microstructures of Al alloys dramatically [2,3,7,19,20,21,22], especially for the precipitated phases induced by Li addition. For instance, the addition of lithium to 0.5 wt.% facilitates the precipitation of θ′ (Al 2 Cu) phase with a refined dispersion in the matrix of 2xxx series aluminum alloys, while higher lithium content (1.0 wt.%) results in the formation of T 1 (Al 2 CuLi) as the dominant precipitant [23].…”
Section: Introductionmentioning
confidence: 99%
“…AES has many applications, mainly revolving around film growth [29][30][31], surface chemical composition [32,33], grain boundaries analysis [34,35], or quality control surface analysis in integrated circuits production [34,36]. Early reports of AES used in implant-related studies date back to 1985 to 1986, when Sundgren et al [37,38] focused on understanding the mechanisms governing reactions occurring at the interface between a stainless-steel implant and tissue.…”
Section: Auger Electron Spectroscopymentioning
confidence: 99%